A pregnant woman with severe dyspnoea. Issue 2 (12th July 2022) - Kanbe, Mio; Yatomi, Masakiyo; Wakamatsu, Ikuo; Uno, Shogo; Hanazato, Chiharu; Aoki-Saito, Haruka; Masuda, Tomomi; Yamaguchi, Koichi; Kasahara, Norimitsu; Miura, Yosuke; Tsurumaki, Hiroaki; Hara, Kenichiro; et al.
Determining the treatment strategies for pregnant women with respiratory failure is difficult. To save the lives of both mothers and children, it is necessary to determine the timing of fetal delivery with the cooperation of not only respiratory physicians but also obstetricians and paediatricians. Preterm delivery is a feasible option in the third trimester of pregnancy in the treatment of pregnant women with acute respiratory distress syndrome due to miliary tuberculosis with respiratory failure https://bit.ly/3stKOzj